Evaluation the effects of blue crab Shell extract on some hematological and biochemical parameters in male rats induced cyclophosphamide. - Dalal Abuqirasah; Fatmah A Matough; Naser M Alaasswad; Ahmad Taha (Journal of Medical Sciences, 2023)
The aim of this study was carried out to determine whether crab Shell extract (CSE) has potential therapeutic and preventive effects when administrated (500 mg) once daily for four weeks would prevent cyclophosphamide-induced hepatotoxicity in albino male rats. Methods: Total of twenty-five male rats were divided randomly into five groups of 5 rats each as follows: negative control group (NC), positive control (PC) group, Normal + CSE, positive control+CSE (PC+CSE) and the Preventive group + CSE. Follow four weeks of treatment Total Protein (TP), liver enzymes include Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), and Alkaline Phosphatases (ALP) and complete blood count (CBC) were measured. Results: There were significantly different in the values of MCV, MCH, MCHC, RBC, WBC, Plt and Hb among all study groups when compared with NC group. PC group had a significantly increased AST level compared to the normal group, and a significantly decreased of AST level among normal+CSE compared to CP+CSE and Preventive group + CSE P=0.003, P= 0.001 respectively. our results also showed that ALT levels were significantly higher (p<0.001) in CP group as compared to CP+CSE group. Decreased levels of ALP (P<0.001), were observed in CP+CSE group when compared to the positive control. on the other hand, there were no significantly different in the total protein among all groups of study. Conclusion: Four weeks of daily supplementation with 500mgof crab Shell extract (CSE) was found to be able significantly improve biochemical and hematological changes caused by cyclophosphamide.